(untitled) (Research, Society and Development, 2021)
Objective: the actual research aims to evaluate the discernment and attitudes of the medical students regarding Primary Health Care. Methodology: This is a cross-sectional, descriptive and analytical study, with students of sixth year of the Medicine course. The material were composed by August to November 2016 with the application of a validated Likert questionnaire titled Attitudes Scale Facing Some Questions of Medical Practice, elaborated at the Medical School of Ribeirão Preto, University of the State of São Paulo. Results: The information were submitted to the statistical test of Chi-square of adherence by the program Bio-Estat 5. There were 111 students participants of the study, number considered sufficient for a statistical validation. From the data analysis of the questionnaires, it was noticed that the medical students recognize the responsability of the general doctor, mainly, in the scope of the approximation of the population with the health services. Conclusion: Accordingly, it becomes evident the need for the persistence of humanized and person-centered perceptions, with a focus on stimulating preventive aspects and promoting a better quality of life in society.